Complement System in Cutaneous Squamous Cell Carcinoma - Pilvi Riihilä; Liisa Nissinen; Jaakko Knuutila; Pegah Rahmati Nezhad; Kristina Viiklepp; Veli-Matti Kähäri (MDPI, 2022)
Epidermal keratinocyte-derived cutaneous squamous cell carcinoma (cSCC) is the most common metastatic skin cancer with high mortality rates in the advanced stage. Chronic inflammation is a recognized risk factor for cSCC progression and the complement system, as a part of innate immunity, belongs to the microenvironment of tumors. The complement system is a double-edged sword in cancer, since complement activation is involved in anti-tumor cytotoxicity and immune responses, but it also promotes cancer progression directly and indirectly. Recently, the role of several complement components and inhibitors in the regulation of progression of cSCC has been shown. In this review, we will discuss the role of complement system components and inhibitors as biomarkers and potential new targets for therapeutic intervention in cSCC.